Study Of The Trend In Piano Education And The Music Literacy In China From The 20th To The 21st Centuries, Including An Attention On Guang XI The Province As A Case Study - Yun, Bai; Ali, Lubna (Journal of Neonatal Surgery, 2025)
The use of game mechanics in both online and conventional classroom settings has become more common in recent years, and this trend is seen across all educational levels. When it comes to improving student motivation and the effectiveness of the learning process, gamification techniques are quickly becoming the preferred method of many educational institutions. In this piece, the researchers look at a game-based learning environment that can facilitate the integration of digital games into the teaching-learning process. Given the emphasis on practical experience, this environment is perfect for acquiring accounting skills via online means. There has been a steady increase in student engagement with the article's game-based virtual classroom for a while now, and that's probably because gamification is gaining traction at the university level.